2022
DOI: 10.1007/s00420-022-01930-z
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators for participation in workplace health promotion programs: results from peer-to-peer interviews among employees

Abstract: Objective Workplace health promotion programs (WHPPs) have shown to be effective in improving lifestyle behaviors of employees. Despite potential benefits for employees, participation rates are generally low. The aim of this study was to gain deeper insight into barriers and facilitators for participation in WHPPs prior to implementation according to employees. Methods Peer-to-peer interviewing, a method derived from citizen science, was used to actively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Ensuring that these concerns are met and that employees have adequate digital skills will be very important in promoting DWHP, paying attention to usability criteria (Hennemann et al, 2018). To increase the likelihood of high acceptance rates and meeting user needs, having employees and WHP professionals co-design (Smit et al, 2023) DWHP programs is recommended. Further research and integrating DWHP as key element for investigations on ICT and health at the workplace will be relevant in the context of its increased use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ensuring that these concerns are met and that employees have adequate digital skills will be very important in promoting DWHP, paying attention to usability criteria (Hennemann et al, 2018). To increase the likelihood of high acceptance rates and meeting user needs, having employees and WHP professionals co-design (Smit et al, 2023) DWHP programs is recommended. Further research and integrating DWHP as key element for investigations on ICT and health at the workplace will be relevant in the context of its increased use.…”
Section: Discussionmentioning
confidence: 99%
“…As determinants of health are multifaceted (Dahlgren and Whitehead, 1991), efforts to promote health and prevent disease need to be specified for the respective setting. In the workplace, examining the barriers and facilitators of participation in WHP is especially relevant (Smit et al, 2023). During the SARS-CoV2pandemic, many companies supplemented elements or completely switched to digital WHP (DWHP) offers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible solution proposed in the literature was to enable participation in the educational aspects of a sleep health program during work hours, thereupon keeping the private life separate from work-related activities. 36 The lack of work-life balance was another barrier that could discourage participation in sleep health programs. With new work structures adopted during COVID-19, additional strain was placed on work-life balance.…”
Section: Discussionmentioning
confidence: 99%
“…Another study exploring barriers to participating in WHPs found that time constraints that would limit participation were evident among employees who showed a preference to keep work and private life separate. A possible solution proposed in the literature was to enable participation in the educational aspects of a sleep health program during work hours, thereupon keeping the private life separate from work-related activities 36 …”
Section: Discussionmentioning
confidence: 99%